Is there an association between social determinants and care dependency risk? A multi‐state model analysis of a longitudinal study. Issue 3 (20th April 2020) - Schneider, Alice; Blüher, Stefan; Grittner, Ulrike; Anton, Verena; Schaeffner, Elke; Ebert, Natalie; Jakob, Olga; Martus, Peter; Kuhlmey, Adelheid; Wenning, Volker; Schnitzer, Susanne
Abstract: Despite a growing body of knowledge about the morbidities and functional impairment that frequently lead to care dependency, the role of social determinants is not yet well understood. The purpose of this study was to examine the effect of social determinants on care dependency onset and progression. We used data from the Berlin Initiative Study, a prospective, population‐based cohort study including 2, 069 older participants living in Berlin. Care dependency was defined as requiring substantial assistance in at least two activities of daily living for 90 min daily (level 1) or 3+ hours daily (level 2). Multi‐state time to event regression modeling was used to estimate the effects of social determinants (partnership status, education, income, and sex), morbidities, and health behaviors, characteristics, and conditions. During the study period, 556 participants (27.5%) changed their status of care dependency. Participants without a partner at baseline were at a higher risk to become care‐dependent than participants with a partner (hazard ratio [HR], 95% confidence interval [CI]: 1.24 (1.02–1.51)). After adjustment for other social determinants, morbidities and health behaviors, characteristics, and conditions the risk decreased to a HR of 1.19 (95% CI: 0.79–1.79). Results indicate that older people without a partner may tend to be at higher risk of care dependency onset but not at higher risk of care dependency progression. Clinicians should inquire about and consider patients' partnership status as they evaluate care needs.